Genome-wide association scan and candidate gene analysis for seed coat color in sesame (Sesamum indicum L.) - Elsafy, Mohammed; Badawi, Wafa; Ibrahim, Ahmed; Hafiz Baillo, Elamin; Bajgain, Prabin; Abdelhalim, Tilal Sayed; Rahmatov, Mahbubjon (Frontiers in Plant Science, 2025)
IntroductionSeed coat color in sesame is a crucial trait for breeding programs as it is closely associated with important characteristics such as oil content, protein levels, and disease resistance, which directly influence seed quality and market value.MethodsThis study investigates the genetic basis of seed coat color in 200 Sudanese sesame genotypes grown for two consecutive years through comprehensive phenotyping, genomic diversity analysis, genome-wide association studies (GWAS), and candidate gene discovery.Results and discussionPhenotypic analysis across two growing seasons revealed high heritability and significant correlations among color parameters (L*, a*, and b*), indicating strong genetic control over seed coat color. The genomic analysis identified distinct clusters among sesame accessions, with rapid linkage disequilibrium decay suggesting a high level of recombination. GWAS identified significant SNPs associated with seed coat color traits, revealing key genomic regions on chromosomes 3, 6, 9, 12, and 13. Candidate gene analysis highlighted several genes, including DOF zinc finger proteins and WRKY transcription factors, which may play essential roles in pigment biosynthesis pathways. These findings provide valuable insights for breeding programs to enhance desirable seed coat color traits in sesame.